Legal Reforms in Indonesia Related to "Presidential Threshold" of Presidential Candidate in Law No. 7 Of 2017 Concerning General Elections - Sidi Ahyar Wiraguna; Faisal Santiago; Zudan Arief Fakrulloh (Journal of Social Research, 2023)
The election is the manifestation of freedom in choosing the president, vice-president and legislature parliament in a country, because the elections play a role as a mechanism for political change regarding the funds patterns for the direction of public policy/or regarding the circulation of the elite periodically and in an orderly manner. Indonesia itself holds the presidential and vice-presidential elections every five years that requires its citizens to vote the potential candidates for becoming the president and vice president for the next 5 years. This research aims to find out the legal reforms related to presidential nomination of Presidential Threshold based on Law number 7 of 2017 concerning the General Elections. This research examines the law concerning the presidential elections and presidential threshold based on 1945 Constitution in Indonesia to find out the president election and the obstacles in its implementation. This research showed that it is possible that public expect more candidate than just two candidates. And the public will only vote for the presidential candidate by dominant party, not the party in accordance with citizens’ need. From this research, it can be concluded that the unnecessary presidential appointments are incompatible with the dignity of Indonesia constitution.